"I didn't Know You were Fighting So Hard for me": Attorneys' Perceptions of Youth Participation in Child Dependency Proceedings. (October 2016) - Augsberger, Astraea; Lens, Vicki; Hughes, Andrea
Abstract : This study examined attorneys' perceptions of youth participation in child dependency proceedings. Surveys and semi‐structured interviews were conducted with attorneys who represent adolescents in child dependency proceedings. Three dimensions of participation were identified: receiving information, providing information, and self‐advocacy. Barriers to youth participation included individual‐level factors, such as the youth or the attorney not wanting the youth to attend, and system‐level factors, such as the scheduling of court hearings, large caseloads, long waits, and cases being adjourned multiple times. Recommendations for enhancing youth participation in child dependency proceedings are presented. Key Points for the Family Court Community: Attorneys play a critical role in representing adolescent clients' wishes and interests in child dependency proceedings; therefore, it is essential to understand how attorneys conceptualize youth participation in court. There are multiple individual and systemic barriers to adolescent participation in dependency proceedings, including the adolescent, the attorney, the judge, and court policies and procedures. In an effort to enhance adolescent participation in court, attorneys and other court actors should receive specialized training focused on adolescent development and communicating with adolescents in the legal realm.